2019
DOI: 10.1021/acs.bioconjchem.9b00505
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin Coupled Lower Generation PAMAM Dendrimers for Brain Targeted Delivery of Memantine in Aluminum-Chloride-Induced Alzheimer’s Disease in Mice

Abstract: Lower generation PAMAM dendrimers have an immense potential for drug delivery with lower toxicity, but these dendrimers yet need certain basic ameliorations. In this study, the brain delivery potential of the synthesized PAMAM-Lf (lower generation PAMAM and lactoferrin conjugate) loaded with memantine (MEM) was explored and evaluated in vitro and in vivo in the disease-induced mouse model. The developed nanoscaffolds were characterized for size, zeta potential and in vitro release. Increase in the average size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Indeed, a strong decrease in choline acetyltransferase activity in the cortex and hippocampus has been related to human memory and cognitive dysfunction in AD patients [ 26 ]. Our data showed that AChE activity decreased in hippocampus of AlCl 3 -exposed rats, which corroborate with recent studies suggesting that the administration of AlCl 3 decreases acetylcholinesterase activity in mouse [ 23 ] and rat brains [ 25 ]. Recently, Martinez et al showed that the dose of 100 mg/kg of AlCl 3 inhibits AChE activity on the hippocampus of rat after 60 days of treatment, confirming the inhibition of cholinergic activity [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, a strong decrease in choline acetyltransferase activity in the cortex and hippocampus has been related to human memory and cognitive dysfunction in AD patients [ 26 ]. Our data showed that AChE activity decreased in hippocampus of AlCl 3 -exposed rats, which corroborate with recent studies suggesting that the administration of AlCl 3 decreases acetylcholinesterase activity in mouse [ 23 ] and rat brains [ 25 ]. Recently, Martinez et al showed that the dose of 100 mg/kg of AlCl 3 inhibits AChE activity on the hippocampus of rat after 60 days of treatment, confirming the inhibition of cholinergic activity [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, this model is increasingly used to study bioactive/chemical molecules potential on the treatment of this pathology and to follow up drug intervention studies. In fact, data on AlCl 3 exposed mice are consistent with the main pathological features (oxidative stress, inflammation and apoptosis) of clinical AD [ 23 , 24 ], indicating that the sporadic AD rat model used in this work meets the experimental AD study requirements. Thus, in the present study, we focused on the therapeutic and recovery effects of CUR on chronic AlCl 3 -exposed rats.…”
Section: Discussionsupporting
confidence: 67%
“…A novel finding has been achieved by coupling the lactoferrin and low-generation dendrimers for brain-targeted delivery of memantine in ADinduced mice. A recent study has reported the significant impact on the memory aspects in target mice (Gothwal et al, 2019).…”
Section: Dendrimersmentioning
confidence: 99%
“…Despite the best results in improving cognitive impairments in patients, the clinical applicability of MEM is limited. MEM should be administered daily, which leads to poor compliance with the drug regimen [205]. The development of nanocarriers with memantine can help to solve these problems.…”
Section: Memantine the Nmda Receptors Antagonistmentioning
confidence: 99%
“…The profile of memantine release from nanoparticles was slow and persisted for up to 48 h. The brain absorption of NPs was significantly higher than that of pure memantine. The in vivo research in an AlCl3-induced AD mice model demonstrated a considerable improving in behavioral tests [205].…”
Section: Memantine the Nmda Receptors Antagonistmentioning
confidence: 99%